Annual review of working conditions in the EU: 2005-2006 - European Foundation for the improvement of living and working conditions (Λουξεμβούργο : Υπηρεσία Επισήμων Εκδόσεων των Ευρωπαϊκών Κοινοτήτων, 2007)
This third annual review of the European Working Conditions Observatory (EWCO) summarises the main developments, at EU level, in the area of working conditions and quality of work and employment. It mainly refers to the period January to December 2005. The analysis follows the paper, Quality of work and employment in Europe: Issues and challenges , compiled by the European Foundation for the Improvement of Living and Working Conditions . The paper identifies four key dimensions necessary for the promotion of quality: • ensuring career and employment security; • maintaining and promoting the health and well-being of workers; • developing skills and competences; • reconciling working and non-working life.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Quality of life -- European Union countries; Labor supply -- European Union countries; Electronic books